PENGARUH PERCEIVED SOCIAL MEDIA MARKETING ACTIVITIES TERHADAP CUSTOMER BASE BRAND EQUITY: Survei Pada Follower Akun Instagram Pixy - Azka Nurul Amani, - (2022)
Azka Nurul Amani (1705335), The Effect of Perceived Social Media Marketing Activities on Customer Based Brand Equity on Pixy Instagram Account Followers. Under the guidance of Dr. Bambang Widjajanta, MM and Lisnawati S.Pd., MM Objectives - The purpose of this study are to determine the description and influence of Perceived Social Media Marketing Activities on Customer-Based Brand Equity on Pixy's Instagram account followers. Design/Methodology/Approach - The type of research used is descriptive and verification. The method used is non-propability sampling with a sample size of 100 respondents. The analytical technique used is the Path analysis using the IBM SPSS version 26.0 program. Findings - The results of this study indicate that the description of Perceived Social Media Marketing Activities is in a fairly good category, Customer-Based Brand Equity is quite good and the influence of Perceived Social Media Marketing Activities on Customer-Based Brand Equity. Originality/Value - The difference in this research lies in the time of the study, the place of research, measuring instruments, literature used, theory used and research results. Keywords: Perceived Social Media Marketing Activities; Customer Based Brand Equity